Legal Analysis of the Criminal Act of Embezzlement in Office that is Continuously Committed: A Case Study of the Decision of the Mempawah District Court - Muhammad Ilham Akbar; Andri Winjaya Laksana (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Information technology systems have now penetrated nearly every aspect of human life, attracting significant attention from people worldwide and transforming their lifestyles. Advances in computer technology have coincided with changes in society, encompassing social values, norms, behavioral patterns, the organization, and the structure of societal institutions. In this context, criminal law forms part of a country's overall legal system. Criminal law is a subset of public law, which regulates the relationship between the state and individuals and the public interest, in contrast to private law, which regulates relationships between individuals and private interests. Acts prohibited by criminal law and punishable by law are known as criminal acts or offenses. In the Criminal Code (KUHP), criminal acts are classified into two types: crimes and violations. Examples of crimes include theft, embezzlement, assault, and murder, while violations include delinquency, begging, and vagrancy. Crime in society develops in line with the development of society itself, as crime is a product of society and needs to be addressed. This is because crime will not disappear on its own; instead, criminal cases are becoming more frequent, with the most dominant type being crimes against property, particularly embezzlement. Crime against property will likely increase in developing countries. This increase is in line with economic development and growth. Crime, as a social phenomenon occurring on earth, will likely never end, in line with the development and social dynamics that occur in society. This criminal problem appears to continue to grow and will never recede, both in terms of quality and quantity. This development causes unrest for both society and the government. Based on the First National Law Seminar in 1963, it was suggested that the purpose of Indonesian criminal law is to prevent obstacles to the creation of the society that the Indonesian people aspire to, by establishing prohibited acts and the penalties threatened to violate these prohibitions. Criminal acts are contrary to the order desired by law and are detrimental to society, and are therefore strictly prohibited. A good legal system will certainly be useless if not enforced. For this, quality resources and supporting facilities and infrastructure are needed. Furthermore, broad public support is a prerequisite for achieving just law enforcement. The use of criminal law with negative sanctions should be viewed as a last resort/subsidiary measure, prioritizing sanctions in other legal fields. If criminal law is to be involved, the lighter sanctions should be used among the many alternative sanctions threatened.